Unsymmetrically substituted imidazolium salts: synthesis, characterization and antimicrobial activity - Esin Poyrazoğlu Çoban; Rukiye Fırıncı; Halil Biyik; Muhammet Emin Günay (Universidade de São Paulo, 2017)
ABSTRACT Unsymmetrically substituted imidazolium salts were synthesized and characterized using 1H-NMR and 13C-NMR. The antimicrobial activities of the salts were evaluated using the agar-well diffusion method against 14 bacteria and five yeasts. The minimal inhibitory concentrations (MIC) against seven bacteria and one yeast were also determined. Among the test compounds applied, 1, 2, 3, 6 and 11 showed activities against Micrococcus luteus ATCC 9341, Staphylococcus aureus ATCC 25923, Staphylococcus epidermidis ATCC 12228, Bacilllus cereus ATCC 11778, Bacillus subtilis ATCC 6633, Bacillus thuringiensis, Listeria monocytogenes ATCC 19112 and Candida trophicalis. However, compounds 1, 2 and 3 showed the highest antimicrobial activities against Micrococcus luteus ATCC 9341, Stapylococcus aureus ATCC 25923, Staphylococcus epidermidis ATCC 12228, Bacilllus cereus ATCC 11778 and Bacillus subtilis ATCC 6633 with inhibition zones of 14-20 mm. In addition, compound 6 have only demonstrated activities against Candida trophicalis while compounds 4, 5, 7, 8, 9, 10, 12, 13 and 14 had no effect on test microorganisms.